2010
DOI: 10.1097/qad.0b013e3283367836
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokine levels during acute HIV-1 infection predict HIV disease progression

Abstract: Background Both T cell activation during early HIV-1 infection and soluble markers of immune activation during chronic infection are predictive of HIV disease progression. Although the acute phase of HIV infection is associated with increased pro-inflammatory cytokine production, the relationship between cytokine concentrations and HIV pathogenesis is unknown. Objectives To identify cytokine biomarkers measurable in plasma during acute HIV-1 infection that predict HIV disease progression. Design Study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
157
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 63 publications
18
157
2
2
Order By: Relevance
“…2 Levels of TNF-a, IL-6, hs-CRP, and other proinflammatory cytokines are associated with HIV-1 viral load and may predict disease progression, as well as correlate with a higher risk of CVD and all-cause mortality. [42][43][44][45] Our findings corroborate another recent analysis, which reported that only d-dimer, and not IL-6 or hs-CRP, is reduced over the short term in those initiating ARV therapy. 46 Additionally, the reductions in LPS observed here are similar in magnitude to those seen in a previous study 47 ; the similar reductions in the DRV/r and ATV/r arms suggest that these ARV agents do not result in differential levels of LPS, a trigger of persistent immune activation in ARV-treated individuals.…”
Section: Discussionsupporting
confidence: 82%
“…2 Levels of TNF-a, IL-6, hs-CRP, and other proinflammatory cytokines are associated with HIV-1 viral load and may predict disease progression, as well as correlate with a higher risk of CVD and all-cause mortality. [42][43][44][45] Our findings corroborate another recent analysis, which reported that only d-dimer, and not IL-6 or hs-CRP, is reduced over the short term in those initiating ARV therapy. 46 Additionally, the reductions in LPS observed here are similar in magnitude to those seen in a previous study 47 ; the similar reductions in the DRV/r and ATV/r arms suggest that these ARV agents do not result in differential levels of LPS, a trigger of persistent immune activation in ARV-treated individuals.…”
Section: Discussionsupporting
confidence: 82%
“…Others cytokine production can increase viral replication, due the activation role in HIV infected cells, including IL-2, IL-4 and interferon type II (IFN-γ) which, primarly, are required in the support to expansion of antiviral T cells and antibody responses 30 . During the acute phase of HIV-1 infection, was showed 36 that elevated plasma levels of inflammatory cytokines are associated with viremia peaks and can even estimate the time at which the CD4+ T count will drop below 350 cells/mm 3 . Thus it would be important low levels of these cytokine in this critical phase.…”
Section: Constant and Intense Inflammatory Status In Both Initial Andmentioning
confidence: 99%
“…In addition to the initial of the infection, in a cohort study of women at high risk for HIV acquisition, Roberts et al 36 observed that IL-12 and IFN-γ levels were significantly associated with lower VL, but IL-15 and IL-7 with higher VL, and the latter also with lower CD4+ count. These authors demonstrated significant rises in IL-1, IL-2 and IL-7 at approximately six weeks after the infection 36 .…”
Section: Constant and Intense Inflammatory Status In Both Initial Andmentioning
confidence: 99%
“…Concentrations of IFN-α and IL-15 increase within the 5 days following the onset of measurable plasma viremia. Subsequently, increased concentrations of TNF-α, MCP-1, IL-6, IL-8, IL-18 and IFN-γ are also detected [16]. Cytokines synthesized in early HIV-1 infection can have a complex effect on the host.…”
Section: Introductionmentioning
confidence: 98%